Pengaruh Profitabilitas, Struktur Modal, Efektivitas Pemasaran terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Food and Beverages yang terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Vania, Salma Ezar (STIE Widya Manggala, 2025)
This study aims to prove the influence of profitability, capital structure and marketing effectiveness on the financial performance of manufacturing companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period. This study uses dependent variables of financial performance, while the independent variables are profitability, capital structure, and marketing effectiveness. The population used is 17 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The data collection technique in the study was carried out using the purposive sampling method. The research sample amounted to 11 companies with a total of 33 observations. The data analysis technique used is the multiple linear regression analysis technique. Based on the results of hypothesis testing, it shows that profitability has a positive effect on financial performance. The capital structure has a negative effect is not significant. Marketing effectiveness has a positive effect on financial performance.